Self-Learning Concept: A solution to Improve Mathematical Literacy Skill of Adults' Without Formal Education - Maulana, Fajri; Setiyowati, Lusy (KEADABAN: Jurnal Sosial dan Humaniora, 2022)
Mathematic is a study that must be comprehended by everyone including adults in order to make life easier in dealing with others. However, how do they obtain mathematical literacy skill without formal education? This research was conducted aiming at examining whether adults implement the concept of self-learning or not, hence their mathematical literacy skill is sufficient enough even without proper formal education. This study employed descriptive qualitative research design. The data were gathered by doing interviews to the respondents. This study revealed that the concept of self-learning is actually applied by adults as a solution to improve their mathematical literacy skills. There was even respondent that conducts all phases of self-learning concept, consequently his mathematical literacy skill is significantly much better than the other respondents. It also reveals that each stage of self-learning concept is useful and indeed affecting learning outcomes.